The relevance of doula in Malaysia / Nur Nilam Sari Aimi Sham, Fatin Izzati Mohamad Nadhri and Muhammad Syafiq Salimi - Sham, Nur Nilam Sari Aimi; Mohamad Nadhri, Fatin Izzati; Salimi, Muhammad Syafiq (Faculty of Communication & Media Studies, 2018)
Doula is a trained professional who provides continuous physical, emotional and informational support to a mother before, during and shortly after the childbirth to help her achieve the healthiest and most satisfying experience possible. This study is done in order to find the relevance of doula in Malaysia. This study involves 280 respondents and a structured questionnaire was used for data collection. All variables were measured through scales previously used by other researchers. The study indicated that for the level of people acceptance towards doula in Malaysia is low (M=2.41). This goes the same with the level of the credibility of doula in Malaysia, the study indicated that it is low (M=2.33). Overall, doula service is still not relevant to be practised in Malaysia (M=2.37).